2015
DOI: 10.2217/epi.15.38
|View full text |Cite
|
Sign up to set email alerts
|

The Regulatory Mechanisms of Intragenic DNA Methylation

Abstract: DNA methylation has crucial roles in gene regulation of mammalian cells. DNA methyltransferases (DNMTs) typically add methyl groups to the cytosine in a CpG dinucleotide context [1]. Approximately 70% of the total number of CpG sites in the mammalian genome are methylated, and intragenic regions account for approximately 40% of methylated CpG sites [2]. However, sites in CpG islands (CGIs), which have an elevated G+C composition, frequently lack DNA methylation and are associated with the promoters of 60% of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 20 publications
1
18
0
Order By: Relevance
“…Methylation in the promoter area is often negatively correlated with gene expression; however, correlation of methylation in the gene body and cis‐gene expression does not show a specific directionality (Lee, Choi, Lee, & Kim, ). Our findings show that stress‐induced hypomethylation of the Oprl1 gene body in msP rats is associated with a decrease in Oprl1 gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…Methylation in the promoter area is often negatively correlated with gene expression; however, correlation of methylation in the gene body and cis‐gene expression does not show a specific directionality (Lee, Choi, Lee, & Kim, ). Our findings show that stress‐induced hypomethylation of the Oprl1 gene body in msP rats is associated with a decrease in Oprl1 gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, such hypermethylation may positively correlate with transcription level, in contrast to repression of the expression due to promoter methylation. However, some studies have shown a negative correlation between intragenic methylation and transcriptional elongation [ 32 ] and splicing [ 33 ]. Moreover, there are also observations that DNA methylation interacts with histone modifications and intragenic methylation contributes to proper transcript elongation by removing repressive epigenetic marks (H3K27me3) and recruiting H3K36me3 marks, which are accumulated in actively transcribed units [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, some studies have shown a negative correlation between intragenic methylation and transcriptional elongation [ 32 ] and splicing [ 33 ]. Moreover, there are also observations that DNA methylation interacts with histone modifications and intragenic methylation contributes to proper transcript elongation by removing repressive epigenetic marks (H3K27me3) and recruiting H3K36me3 marks, which are accumulated in actively transcribed units [ 32 ]. With regard to the MC4R gene it was shown that methylation of its coding region in mice is influenced by diet [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Advances in genome-wide approaches have demonstrated that methylation varies depending upon the specific genomic context. Although the majority of studies have focused on methylation in the promoter region adjacent to the transcription start site (TSS), methylation of the gene body or intergenic regions seems to have a functional role and contributes to defining the whole picture of the methylation status [33]. …”
Section: Discussionmentioning
confidence: 99%